Evaluation of the Grade of Hatching Eggs of Sensi-1 Agrinak and KUB Crossbred Chicken on Hatching and Production Performances - Aulia Fitriawati Polontalo; Rudi Afnan; Sri Darwati; Andi Yulyani Fadwiwati (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
The potential of Sensi-1 Agrinak and KUB crossbred so-called SENKUB chicken as dual-purpose chicken can be increased by selecting hatching egg weights to get DOC with good quality. The study was conducted to evaluate the grades of hatching eggs of SENKUB chicken on hatching and production performances. The complete randomized design was applied in this experiment with 3 treatments. The treatments are the grades of hatching egg (small 36-40 g, medium 41-45 g, and large 46-50 g). The hatching process used two stages hatching machine. All DOCs were selected according to the Indonesia National Standard (SNI). The selected DOCs were raised in different pens to evaluate the production performances. The hatching showed that the large eggs have significantly the highest fertility, hatchability, hatching weight, and salable chick but the lowest weight loss. Embryo mortality was the same between different hatching egg grades. The best-weight DOC was obtained from medium and large hatching eggs. The hatching egg grades do not significantly affect the production performances of the hatched chicken. However, the chickens with small and large hatching eggs resulted in better production performance.